Ordered mesoporous alumina with tunable morphologies and pore sizes for CO₂ capture and dye separation - Seah, Geok Leng (2021)
We describe a versatile and scalable strategy toward long-range and periodically ordered mesoporous alumina (Al2O3) structures by evaporation-induced self-assembly of a structure-directing ABA triblock copolymer (F127) mixed with aluminum tri-sec-butoxide-derived sol additive. We found that the separate preparation of the alkoxide sol-gel reaction before mixing with the block copolymer enabled access to a relatively unexplored parameter space of copolymer-to-additive composition, acid-to-metal molar ratio, and solvent, yielding ordered mesophases of two-dimensional (2D) lamellar, hexagonal cylinder, and 3D cage-like cubic lattices, as well as multiscale hierarchical ordered structures from spinodal decomposition-induced macro- and mesophase separation. Thermal annealing in air at 900 °C yielded well-ordered mesoporous crystalline γ-Al2O3 structures and hierarchically porous γ-Al2O3 with 3D interconnected macroscale and ordered mesoscale pore networks. The ordered Al2O3 structures exhibited tunable pore sizes in three different length scales, <2 nm (micropore), 2-11 nm (mesopore), and 1-5 μm (macropore), as well as high surface areas and pore volumes of up to 305 m2/g and 0.33 cm3/g, respectively. Moreover, the resultant mesoporous Al2O3 demonstrated enhanced adsorption capacities of carbon dioxide and Congo red dye. Such hierarchically ordered mesoporous Al2O3 are well-suited for green environmental solutions and urban sustainability applications, for example, high-temperature solid adsorbents and catalyst supports for carbon dioxide sequestration, fuel cells, and wastewater separation treatments.